A Biologically Inspired and Protein-Based Bio-Cyber Interface for the Internet of Bio-Nano Things - Pit Hofmann; Juan A. Cabrera; Gunnar Schulte; Frank H.P. Fitzek (Biosensors and Bioelectronics: X)
The Internet of Things (IoT) has changed the way how we interact with our physical environment, enabling connectivity and communication between physical and virtual entities, e.g., for digital twin applications. However, as we step beyond the IoT, developing the Internet of Bio-Nano Things (IoBNT), where biological and nanoscale entities will be included in our communication networks, includes challenges as well as opportunities. In the IoBNT, the role of Bio-Cyber Interfaces (BCIs) is still underscored, representing necessary building blocks that ensure the bidirectional information exchange between biological and digital communication systems. The application area of the IoBNT spans diverse domains, e.g., healthcare, personalized medicine, or environmental monitoring. This work proposes a theoretical framework for a BCI, leveraging advances in biotechnology, nanotechnology, and communication engineering to establish an interface for exchanging information between biological entities, nanoscale devices, and the digital world. Therefore, we discuss the key components of the proposed BCI framework. Furthermore, we survey the existing literature of biologically inspired BCIs and outline potential use cases and benefits of integrating BCIs in the IoBNT for various domains, such as healthcare and environmental monitoring.